the administrative investigation and its impact on the performance of the offices of the inspectors General. - ابراهيم نوال طارق; علوان محمد حسين (Journal of Economics and Administrative Sciences, 2018)
The purpose of this research is to highlight the relationship between the administrative investigation and the improvement of institutional performance, and the research sought to achieve a set of cognitive and applied goals. the administrative investigation is the modern trend of managing the offices of the general hginspectors and the main source to build the necessary standards to manage and invest its resources efficiently and effectively required to achieve the goals it seeks. The institutional performance is the cornerstone for the implementation of all tasks and duties carried out by institutions operating within the borders of a particular country, The significant changes in the environment in which the offices of the Inspectors are operating are many, many of which are looking for ways to help them achieve many of their competitive advantages. The problem of research was that there is a clear lack of application of the administrative investigation and the omission of its role in improving the institutional performance of the investigated offices. Based on this problem and the objectives, and to clarify the relationship between the main and secondary research variables, The questionnaire was used as a tool for collecting data and information related to research. It was prepared on the basis of a number of ready-made measurements and the use of the Lycert quintet. The questionnaire was distributed to a sample of 40 staff members of the inspectors’ offices in Diyala Governorate. To analyze the research data, use SPSS and Excel. The statistical methods produced a number of results, most notably the existence of a significant correlation between the administrative investigation and the improvement of the institutional performance, and it emerged that there is a significant effect for all dimensions of the quality of the administrative investigation in improving the institutional performance indicators of the investigated institution. In the context of discussing the results, the study presented a number of conclusions, the most important of which is that the administrative investigation is the most important sources for improving the institutional performance of the research institution in light of the dynamic environment in which it operates, which necessitates increasing the interest in applying its indicators to learn about the experiences of developed countries in this field Form possible.